The E3 ubiquitin ligase SCF(Fbxo7) mediates proteasomal degradation of UXT isoform 2 (UXT-V2) to inhibit the NF-κB signaling pathway - Spagnol, Valentine; Oliveira, Caio A.B.; Randle, Suzanne J.; Passos, Patrícia M.S.; Correia, Camila R.S.T.B.; Simaroli, Natália B.; Oliveira, Joice S.; Mevissen, Tycho E.T.; Medeiros, Ana Carla; Gomes, Marcelo D.; Komander, David; Laman, Heike; et al. (Biochimica et biophysica acta. General subjects, 2021)
Ubiquitously eXpressed Transcript isoform 2 (UXTV2) is a prefoldin-like protein involved in NF-κB signaling, apoptosis, and the androgen and estrogen response. UXT-V2 is a cofactor in the NF-κB transcriptional enhanceosome, and its knockdown inhibits TNF-α -induced NF-κB activation. Fbxo7 is an F-box protein that interacts with SKP1, Cullin1 and RBX1 proteins to form an SCF(Fbxo7) E3 ubiquitin ligase complex. Fbxo7 negatively regulates NF-κB signaling through TRAF2 and cIAP1 ubiquitination. We combine co-immunoprecipitation, ubiquitination in vitro and in vivo, cycloheximide chase assay, ubiquitin chain restriction analysis and microscopy to investigate interaction between Fbxo7 and overexpressed UXT-V2-HA. The Ubl domain of Fbxo7 contributes to interaction with UXTV2. This substrate is polyubiquitinated by SCF(Fbxo7) with K48 and K63 ubiquitin chain linkages in vitro and in vivo. This post-translational modification decreases UXT-V2 stability and promotes its proteasomal degradation. We further show that UXTV1, an alternatively spliced isoform of UXT, containing 12 additional amino acids at the N-terminus as compared to UXTV2, also interacts with and is ubiquitinated by Fbxo7. Moreover, FBXO7 knockdown promotes UXT-V2 accumulation, and the overexpression of Fbxo7-ΔF-box protects UXT-V2 from proteasomal degradation and enhances the responsiveness of NF-κB reporter. We find that UXT-V2 colocalizes with Fbxo7 in the cell nucleus. Together, our study reveals that SCF(Fbxo7) mediates the proteasomal degradation of UXT-V2 causing the inhibition of the NF-κB signaling pathway. Discovering new substrates of E3 ubiquitin-ligase SCF(Fbxo7) contributes to understand its function in different diseases such as cancer and Parkinson. •UXT-V2 is a canonical substrate of SCF(Fbxo7) E3 ubiquitin ligase.•Fbxo7 interacts with both UXT-V1 and UXTV2.•UXT-V2 recruits Fbxo7 to the cell nuclei.•Fbxo7 inhibit NF-kB pathway through degradation of UXT-V2.